Analysis of the efficacy of a method for the early detection of male athletic sprinters - Baide-Ordoñez, F. R.; Cordovés-Peinado, R. (Journal of Human Sport & Exercise, 2020)
The research was carried out on a topic relevant to athletics, its objective was to analyse the effectiveness of a method for the early detection of male sprinters in this discipline. The idea arose from the problem taking into account the absence of a scientific way or form in Honduran athletics to guarantee the effectiveness in said process, this being a primary phase in sports initiation which is of interest to coaches, for the Honduran Federation of Athletics and the Honduran Olympic Committee as its main sponsor. The study was based on the main methods and procedures that allowed to establish the routes for the selection of talent in the area of speed, the sample of a group of children from the Garifuna coastal communities was determined for their possible inclusion in the Honduran Olympic Committee; Results were obtained in the proposed phases of identification and selection, the first allowed to determine the sports aptitude with an approach to the speed tests and the second agreed to measure the state of speed and its indicators in preparation process to specify the selection of talent , obtaining results of the functionality of the contribution after the application of tests, also the correlation between them by means of the Pearson coefficient, the expert criterion showed the acceptance of a group of competent specialists in the subject, considering that the methodology can be established.